Designing Three‐dimensional (3D) Non‐Fullerene Small Molecule Acceptors with Efficient Photovoltaic Parameters. Issue 45 (4th December 2018) - Ans, Muhammad; Iqbal, Javed; Ahmad, Zahoor; Muhammad, Shabbir; Hussain, Riaz; Eliasson, Bertil; Ayub, Khurshid
Abstract: Three dimensional (3D) acceptor‐donor‐acceptor (A−D‐A) type small molecules (M1, M2, M3 andM4) are theoretically investigated for optoelectronic properties. The designed molecules contain spirobifluorene as core unit linked with end capped acceptors through four four thieno‐[3, 2‐b]Thiophene (TT) units. The end capped acceptors are (3‐methyl‐2‐thioxothiazolidin‐4‐one) (M1 ), 2‐(2‐ethylidene‐5, 6‐difluoro‐3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile (M2 ), 2‐(3‐ethyl‐4‐oxothiazolidin‐2‐ylidine)malononitrile (M3 ) and 2‐(2‐ethylidene‐5, 6‐dicyano‐3‐oxo‐2, 3‐dihydroinden‐1‐ylidene)malononitrile (M4 ). The photovoltaic parameters of the designed molecules are compared with the recently reported reference compoundR . Among all designed molecules, M4 is a low energy gap material (2.28 eV), broad absorption which is attributed to excellent communication between strong electron withdrawing end capped acceptors through extended conjugation. All newly designed molecules have lower binding energy as compared to reference molecule R which results in higher exciton dissociation in excited state. The reorganization energy calculations indicate good charge transfer ability of the designed molecules.M4 shows the lowest λe (0.0022) value with respect to the reference moleculeR (0.034) which signifies its enhanced electronic transport behavior. The calculated open circuit voltages (Voc ) ranges from 1.97 to 2.36 eV, 2.11 to 2.49 eV and 1.9 eV to 2.28 eV with respect to three different well known donor materials PTB7‐Th, PBDB−T and P3HT, respectively. Abstract : Four new 3D small molecule namely M1, M2, M3 and M4 were designed by taking spirobifluorene as a core unit, thieno‐[3, 2‐b]Thiophene as donor moiety and different end capped acceptors groups. The photovoltaic parameters of newly designed molecules were calculated and compared with well‐known reference molecule R. All the newly designed molecules shows good photovoltaic parameters.